Over view of major traumatic injury in Australia––Implications for trauma system design. Issue 1 (January 2020) - Cameron, P.A.; Fitzgerald, M.C.; Curtis, K.; McKie, E.; Gabbe, B.; Earnest, A.; Christey, G.; Clarke, C.; Crozier, J.; Dinh, M.; Ellis, D.Y.; Howard, T.; et al.
Highlights: Trauma registries are known to drive improvements and optimise trauma systems worldwide. This is the first reported comparison of the epidemiology and outcomes at major centres across Australia. The Australian Trauma Registry collected data on 8423 patients with a major injury (ISS > 12 or death after injury) from collaborating major trauma centres across Australia at the time of this study. The median (IQR) ISS was 17 (14–25) with a predominance of males (72%) apart from the extremes of age. Transport-related cases accounted for 45% of major trauma, followed by falls (35.1%). Patients took 1.42 (1.03–2.12) h to reach hospital and spent 7.10 (3.64–15.00) days in hospital. Risk adjusted length of stay and mortality did not differ significantly across sites. Australia has the capability to identify national injury trends to target prevention and reduce the burden of injury. Abstract: Background: Trauma registries are known to drive improvements and optimise trauma systems worldwide. This is the first reported comparison of the epidemiology and outcomes at major centres across Australia. Methods: The Australian Trauma Registry was a collaboration of 26 major trauma centres across Australia at the time of this study and currently collects information on patients admitted to these centres who die after injury and/or sustain major trauma (Injury Severity Score (ISS) > 12). Data from 1 July 2016 to 30 June 2017 were analysed. Primary endpoints were risk adjusted length of stay and mortality (adjusted for age, cause of injury, arrival Glasgow coma scale (GCS), shock-index grouped in quartiles and ISS). Results: There were 8423 patients from 24 centres included. The median age (IQR) was 48 (28–68) years. Median (IQR) ISS was 17 (14–25). There was a predominance of males (72%) apart from the extremes of age. Transport-related cases accounted for 45% of major trauma, followed by falls (35.1%). Patients took 1.42 (1.03–2.12) h to reach hospital and spent 7.10 (3.64–15.00) days in hospital. Risk adjusted length of stay and mortality did not differ significantly across sites. Primary endpoints across sites were also similar in paediatric and older adult (>65) age groups. Conclusion: Australia has the capability to identify national injury trends to target prevention and reduce the burden of injury. Quality of care following injury can now be benchmarked across Australia and with the planned enhancements to data collection and reporting, this will enable improved management of trauma victims.